The Effects of Moderate Aerobic Activity on Short-Term and Long-Term Memory - Brooks, Hannah; Landry, Kaitlyn; Malas, Kareem; Rihal, Naveen; Umhoefer, Heidi (Journal of Advanced Student Sciences (JASS), 2015)
Physical stress induced by moderate aerobic exercise leads to the release of hormones that increase blood flow and nutrient availability to the brain. Research has shown that these changes could be beneficial for long-term memory retention, possibly leading to improved ways to study and memorize material. The current study hypothesized that those performing aerobic activity while participating in memorization tasks would perform better on a long-term memory test. A difference in performance on short-term memory tests was not predicted. 32 participants were given a list of 50 random word pairs and given ten minutes to study, either while stationary or while riding an exercise bike. All participants then took a five minute fill-in-the-blank memory test both immediately after the study period and again one week later. The scores were analyzed using a Welch’s two sample t-test. No statistically significant evidence was found to support the role of exercise in improving long-term or short-term memory retention.
An article that appeared in JASS, issue 2015
Keywords: aerobic; cognitive recall; memory; word recognition; memory retention; visual; blood pressure; long term memory; short term memory; working memory; exercise; oxygen saturation; heart rate; pulse; moderate; word pairs